178 Prediction of Optimal Intervals of Radiological Surveillance for Workers at Different Risks of Silicosis - China's Experience. (11th October 2013) - Tse,; Chen,; Zhang,; Yu,; Wong,; Leung,; Kromhout,; Meijer,; Chen,
Abstract : Objectives: To determine the optimal intervals of chest radiographic surveillance for workers at different risks of silicosis. Methods: All 3492 workers who were exposed to silica dust during 1964–74 in an iron-ore of China were recruited into this historical cohort study, and followed up till 31/12/2008. We obtained worker's information on socio-demographics, smoking habits, disease history, and lifetime occupational history; these variables were used to develop a risk score system according to a prediction model. The discriminative ability of prediction model was determined by the area under the receiver operating characteristic (ROC) curve. We determined the optimal interval of radiographic surveillance for workers at different risk of silicosis according to the OSHA's precedent role (unacceptable risk: >1/1000). Results: The model with the best fit was the least absolute shrinkage and selection operator (LASSO) Cox model which showed a good discrimination with an area of 0.83 (95% CI, 0.81–0.86) under the ROC curve. We classified workers into 3 risk groups according to the score chart, and found the observed probabilities matched well to the predictions. According to the OSHA's precedent role, we can determine that the initial interval of radiographic surveillance for workers in the low risk group (score <25) was 11 years and then a biyearly examination was recommended. The initial examination interval was 11 years and 5 years respectively for workers in the middle (score: 24–40) and high risk group (score ≥40), and a yearly examination was recommended thereafter. For patients with silicosis, an annual radiological surveillance program was recommended regardless of the stage of pneumoconiosis. Conclusions: This study is the first to provide scientific evidence on the optimal intervals of radiographic surveillance for workers at different risk levels of silicosis, whilst cross-setting industry validation in subsequent studies may worth exploring. Acknowledgement: Pneumoconiosis Compensation Fund Board, Hong Kong.